Synergistic Antibacterial Activity of Combined Antimicrobials and the Clinical Outcome of Patients With Carbapenemase-Producing Acinetobacter baumannii Infection - Qu, Junyan; Yu, Rujia; Wang, Qujue; Feng, Chunlu; Lv, Xiaoju (Frontiers in Microbiology, 2020)
The aim of this study was to explore the activity of combined antimicrobials in vitro, and the relationship among resistance mechanisms, antimicrobials regimens, and clinical outcome of patients with carbapenem-resistant Acinetobacter baumannii (CRAB) infections in western China. A total of 89 CRAB strains were collected from patients with CRAB infection from January 2018 to June 2018 in our hospital. The checkerboard assay was performed to study the combination effects in vitro. Carbapenemase-encoding genes were detected by polymerase chain reaction (PCR) or multiplex PCR technique. Clinical data of 86 patients were collected. CRAB showed high susceptibility to tigecycline (91.01% inhibition) and polymyxin (83.15% inhibition). Polymyxin plus sulbactam exhibited the highest synergistic effect at a rate of 82.35%. Production of carbapenemase (blaOXA-23) was the main resistance mechanism of CRAB to carbapenem (95.35%). Excessive expression of active efflux pump genes (adeB, adeJ, and abeM) and deletion of the CarO protein accounted for 13.95% (12/86) and 84.88% (73/86), respectively. Synergistic effect of the sulbactam-based combination was higher than that of the polymyxin B-tigecycline combination for carbapenemase-producing CRAB (P＜0.05). The clinical outcome was not affected by the resistance mechanisms (P＞0.05). Advanced age, multiple organ dysfunction syndrome (MODS), and admission to the intensive care unit (ICU) were associated with treatment failure (P＜0.05). Appropriate antibiotic therapy did not improve the clinical outcome of critically ill patients. Higher minimum inhibitory concentrations (MICs) of tigecycline were associated with treatment failure (P＜0.05). Multivariate analysis showed that ICU stay (OR = 15.123, 95% CI: 2.600-87.951, P =0.002) and procalcitonin≥2 ng/ml (OR = 2.636, 95% CI: 1.173-5.924, P =0.019) were the risk factors for treatment failure. In conclusion, this study demonstrated that the sulbactam-based combination exhibited a synergistic effect in vitro. The clinical outcome of patients was not associated with the resistance mechanisms. Early control of the progression of infection to severe disease may be more important.